Development of SAVI-Based Basic Chemical Law E -Module - Juwita, Syita Auliah; Enawaty, Eny; Sasri, Risya (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Abstract The purpose of this study was to determine the validity of the SAVI-based basic chemical law e-module and to determine students’ responses to the SAVI-based basic chemical law e-module. This study was conducted at SMA Negeri 5 Pontianak, Class XI Chemistry Major. This type of research is Research & Development (R&D), using the ADDIE development model (analysis, design, development, implementation, evaluation) with limitations on the development stage. The results of the study indicate that the developed SAVI-based basic chemical law e-module is included in the very feasible and feasible category with validation results from material experts of 97% (Very Valid), validation from language experts of 100% (Very Valid), validation from media experts of 96.13% (Very Valid), the results of the limited response test conducted by 12 students in class XI Chemistry majoring in three assessment aspects are categorized as very good with details of the module display aspect of 93.75% (Very Good), the material presentation aspect of 93.22% (Very Good), and the benefit aspect of 93.22% (Very Good), and the results of the extensive response test conducted by 24 students in class XI Chemistry majoring in the module display aspect showed a score of 93% (Very Good), the material presentation aspect of 93.48%, and the benefit aspect of 94.53% (Very Good). This shows that the SAVI-based basic chemical law e-module is very feasible to use in the learning process.